Announcing for broadcasting and the internet : the modern guide to performing in the electronic media - Hausman, Carl, 1953-; Benoit, Philip, 1944-; Messere, Fritz (New York: Routledge, 2019)
"Announcing for Broadcasting and the Internet is the standard text for traditional broadcasters and emerging pioneers. While many still pursue careers in traditional fields such as television and radio news announcing, broadcast performance has expanded to Internet radio, podcasting, home voice-over production, and performance on YouTube and other internet video venues. This text is an update of the classic text Announcing. The practical guide to mastering the techniques and mechanics of broadcast announcing remains, updated to give readers the ability to produce their own portfolio of performance products and get started in the career they want. It covers audio and video editing programs, new streaming media, and how to develop a powerful, consistent, and noteworthy speaking voice"--
The communicator in modern media -- Improving your speaking voice -- Understanding the message -- Communicating the message -- Radio staff announcing today -- News announcing basics -- Television news announcing -- The craft of interviewing -- Television and radio specialties -- Commercials and acting -- Polishing your skills -- The new media frontier and the independent performer -- Podcasting -- Internet video -- Home-based narration and voice-over -- Career advancement.
Keywords: Radio announcing -- Vocational guidance; Television announcing -- Vocational guidance; Internet announcing -- Vocational guidance